Toxicity of Polytrin-C on the Psychopharmacological Observations in Wistar Rat - SEKAR BABU HARI RAM; CH.UMADEVI; GOWRI REDDY; T.M.VIJAYAKUMAR; G.THIRUMURUGAN (International Journal of Pharma and Bio Sciences, 2010)
The work has been designed to asses the neuro toxicity of a combination pesticide through behavioral parameters [Psychopharmacological observation] and instrumental analysis such as spontaneous motor activity for 28 days. The mixed formulation selected for the study, polytrin-C was used for sub acute and acute toxicity studies on Wister rats weighing around 90-120 gms of either sex.. Acute studies were carried out to fix the LD 50 dosage of the selected pesticide. Based on the LD 50 values the sub acute doses were fixed [1/40th, 1/20th, 1/10th of the LD 50 Dosage]. It is evident from the results that 1/20 and 1/10 of LD 50 dosed animals of either sex showed marked differences in the behavioral patterns when compare to 1/40 of LD 50 dose animals. Due to the synergetic effect neurotoxicity symptoms of combination pesticide results show a different toxicological profile when compare with the toxicity of constituent pesticide.